2008
DOI: 10.1111/j.1467-8659.2008.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Character Animacy and Preparatory Motion on Perceptual Magnitude of Errors in Ballistic Motion

Abstract: An increasing number of projects have examined the perceptual magnitude of visible artifacts in animated motion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
1
18
2
Order By: Relevance
“…Reitsma et al[2008] found that observers tend to overestimate the effect of gravity on ballistic motion. This may explain the low sensitivity to decreases in velocity in the Ramp block.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Reitsma et al[2008] found that observers tend to overestimate the effect of gravity on ballistic motion. This may explain the low sensitivity to decreases in velocity in the Ramp block.…”
Section: Resultsmentioning
confidence: 96%
“…In this experiment, we evaluated observers' sensitivity to physical distortions in virtual throwing animations. As previous results showed a greater sensitivity to physical distortions on virtual human characters rather than on simple objects [Reitsma et al 2008], we studied the effect of using both a biological human throw and a simple physical simulation (free fall of a ball on a ramp). The results show that observers' sensitivity to errors depends on the animacy of the thrower.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has suggested that preparatory motion may also be an important consideration in the perceived visual quality of ballistic motion [26]. Our method does not address the preparatory or recovery phases of ballistic motion, and leaves such a task to the animator.…”
Section: Ballistic Motionsmentioning
confidence: 99%
“…Perceptual properties of these artifacts depend on many parameters, such as the character's representation [HOT98, CHK07, MJH * 07], the number of character models or animations [MLD * 08], or the artifact's type [RAP08]. The perceptual effects of a variety of anomalies in human animation was also recently studied by Hodgins et al [HJO * 10].…”
Section: Introductionmentioning
confidence: 98%